ANALYZING THE USE OF DOUBLE NEGATIVES IN THE LYRICS OF 15 ENGLISH SONGS - Vivi Anggraini Ramadhania (ETNOLINGUAL, 2022)
English has a lot of grammar elements that are very important to note in order to be used appropriately. One of the easiest ways for English learners to learn English grammar is through the song. The song is very often used as a source of learning English because it has meaningful lyrics and interesting tones. Many of the songs in English do not follow proper grammar. This is created by the songwriter so that the rhyme produced is in accordance with the aesthetic requirements of the song. When the error is not corrected, the error will occur repeatedly both spoken and written English. This study aims to analyze the use of double negatives found in the lyrics of 15 English songs. The use of double negative in proper grammar is an important element of the effective source in learning English. The methods of this study are first analyzing the use of double negatives in the 15 songs lyrics and second classifying the types of double negatives that have been determined based on their criteria. The finding shows there were 15 English songs contain lyrics with double negatives. There are fifteen songs from fifteen popular singers i.e. Adele, Sia, Galantis, Doja Cat, Drake, Cadmium ft. Rosendale, Rae Sremmurd, CHIC, Bruno Mars, Marvin Gaye, Queen, Rihanna, Pink Floyd, Elvis Presley, and Eddie & The Hot Rods.